Women and Migration Responses in Art and History - Willis, Deborah; Toscano, Ellyn; Brooks Nelson, Kalia (Open Book Publishers, 2019)
"The essays in this book chart how women's profound and turbulent experiences of migration have been articulated in writing, photography, art and film. As a whole, the volume gives an impression of a wide range of migratory events from women's perspectives, covering the Caribbean Diaspora, refugees and slavery through the various lenses of politics and war, love and family. The contributors, which include academics and artists, offer both personal and critical points of view on the artistic and historical repositories of these experiences. Selfies, motherhood, violence and Hollywood all feature in this substantial treasure-trove of women's joy and suffering, disaster and delight, place, memory and identity. This collection appeals to artists and scholars of the humanities, particularly within the social sciences; though there is much to recommend it to creatives seeking inspiration or counsel on the issue of migratory experiences."